Controllable synthesis of cube-like ZnSnO3@TiO2 nanostructures as lithium ion battery anodes. Issue 6 (23rd December 2014) - Qin, Yu-ling; Zhang, Fei-fei; Du, Xin-chuan; Huang, Gang; Liu, Ya-cheng; Wang, Li-min
Abstract : Cube-like porous ZnSnO3 @TiO2 has been prepared. Furthermore, it exhibits excellent cycle stability and rate capability for LIBs. Abstract : ZnSnO3 is an attractive anode material for lithium ion batteries because of its higher theoretical capacity compared to the state-of-the-art carbonaceous counterpart. The main challenges associated with ZnSnO3 anodes are structural degradation and instability of the solid-electrolyte interphase, caused by the large volume change during cycling. Herein, we propose a hierarchical structured ZnSnO3 @TiO2 nanocomposite anode that tackles this problem. The as-prepared, core–shell, cube-like anode material exhibits enhanced capacity and cycling property. In proof-of-concept experiments, this hierarchical heterostructure shows a high initial discharge capacity of 1590 mA h g −1 at 100 mA g −1 and retained 780 mA h g −1 after 200 cycles, which is much better than the anodes made of pure ZnSnO3 nanomaterials. The enhanced cycle life can be attributed to the reductive volume expansion during the repeated charge–discharge cycles, owing to the hierarchical porous three-dimensional structure and TiO2 shell as well as the synergistic effects of ZnSnO3 and TiO2 .